2010
DOI: 10.3892/ol_00000081
|View full text |Cite
|
Sign up to set email alerts
|

The human pluripotency gene NANOG/NANOGP8 is expressed in gastric cancer and associated with tumor development

Abstract: Abstract.It is well known that cancer cells exhibit characteristics similar to normal stem cells. The majority of tumors frequently overexpress genes commonly found in embryonic stem cells. To determine whether the pluripotency gene NANOG and its retrogene, NANOGP8, play a role in gastric cancer, we analyzed the NANOG/NANOGP8 expression profile at the mRNA and protein level in primary gastric tumors. Our data demonstrated that overexpression of NANOG/NANOGP8 was consistently detected in primary tumors (75%, 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…A similar result was found by Zhang et al. () in gastric cancer, correlating NANOG overexpression with the initial steps of gastric carcinogenesis (Zhang et al., ). Ye, Zhou, Cheng, Shen, and Chen () studied NANOG expression in normal cervical tissue, cervical tissue with dysplasia (mild, moderate, and severe), and cervical squamous cell carcinoma, and found higher expression of NANOG in dysplastic tissues than in normal tissues (Ye et al., ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A similar result was found by Zhang et al. () in gastric cancer, correlating NANOG overexpression with the initial steps of gastric carcinogenesis (Zhang et al., ). Ye, Zhou, Cheng, Shen, and Chen () studied NANOG expression in normal cervical tissue, cervical tissue with dysplasia (mild, moderate, and severe), and cervical squamous cell carcinoma, and found higher expression of NANOG in dysplastic tissues than in normal tissues (Ye et al., ).…”
Section: Discussionsupporting
confidence: 87%
“…() found NANOG mainly located in the nucleus of rat embryonic cells (Liang et al., ). However, variations in intracellular distribution were found in different types of neoplasms as predominantly nuclear in OSCC, predominantly cytoplasmic in colorectal cancer cells, and both in gastric cancer cells (Chiou et al., ; Meng et al., ; Watanabe et al., ; Zhang et al., ). In this study, NANOG was found in both nucleus and cytoplasm with significant correlation between AC and LSCC cases, suggesting that nuclear and cytoplasmic expression would be coordinated and both would influence neoplastic progression.…”
Section: Discussionmentioning
confidence: 99%
“…Due to and Nanog, reciprocal regulation of these proteins is suggested in governing pluripotency and self-renewal of ESCs . Interestingly, overexpression of OCT4 and Nanog has been shown in a gastric cell line and samples (Zhang et al, 2010;Huang et al, 2012). These data, along with SALL4 overexpression, which is reported here, lead us to hypothesize the existence of similar activated regulatory transcriptional networks in gastric cancer playing essential roles in proliferation and self-renewal characteristics of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 1-3 % of carcinogenic cells are CD133? and that these cells possess higher clonogenicity, invasiveness, and increased in vivo tumorigenicity as compared to their CD133-counterparts (Zhang et al 2010a). The present results support these observations, implying the potential of using CD133 as a CSC surface marker present on human tumoral specimens.…”
Section: Discussionmentioning
confidence: 97%
“…CD133 has been used as a marker to identify CSCs derived from primary solid tumors in the head and neck region (Zhang et al 2010a;Hsu et al 2011). Furthermore, expression of CD133 is a prognostic marker of survival in SCC (Zhang et al 2010b).…”
Section: W Limmentioning
confidence: 99%